CONTROVERTION BETWEEN TEXT VERSUS CONTEXT IN INTERPRETING AL-QUR'AN - Muhammadong, Muhammadong; Junaedi, Dedi (Program Pascasarjana, UIN Alauddin Makassar, 2021)
The controversy referred to in this paper is not to find a clash with the qath'i texts, but to find a common perception of the two propositions so as to find the point of truth. The controversy surrounding the issue of text versus context will never be resolved because the existence and urgency of the Qur'an revealed are global in nature so that a broader interpretation is needed to give benefit to humans to be able to be applied in human muamalat problems. In understanding the propositions that are already qath'i, sometimes it is found groups who use the text approach and then use the context approach in different situations. So it is considered confusing among Muslims. Whereas the existence of the Qur'an as a revealed book is very adaptive to various problems so it must be elaborated based on the demands of the circumstances and time.